Pemeliharaan Planaria Dalam Perkembangbiakan Secara Vegetatif - Surtikanti, Hertien Koosbandiah (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
Test organism which is used for bioassay must fulfill some criteria such as: high sensitifity, widely available, wide distribution, biology background, successfully maintained in laboratory, and known history of culture in laboratory. This research has been done to study regeneration (vegetative) process of Planaria under laboratory condition. This is studied because of limited number of planaria population in clean freshwater. In order to study regeneration process, combination of two treatments (water conductivity and division-cutting type) were done to obtain optimum culture of Planaria. Four water conductivity (100, 200, 300 and 400 Î¼S/cm) and four division-cutting types (whole longitudinal, half longitudinal, transversal above pharynx and transversal mid-pharinx) were used. Each individual of Planaria was exposed with those treatments for 10 days (October, 2002). Initial and completed growth were observed. The result showed that, regeneration process of Planaria took 3-6 days to get full growth after transversal cutting (mid-pharynx). Whole summary revelead that Planaria is easy to maintain in laboratory. Therefore, Planaria may be used as an alternative bioindicator in evaluating water pollution.